1992
DOI: 10.1111/j.1365-2273.1992.tb01841.x
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of otitis media with effusion in adults and children

Abstract: A prospective study of otitis media with effusion (OME) in both adults and children has been carried out. 75 new adult patients were seen during a 4-year period. Of these, 13 had associated diseases which could reasonably be considered to have been a cause of their effusion. Over a 2-year period, 192 new children with OME were seen. There was a significantly higher incidence of previous otalgia and/or aural discharge in the children as compared to the adults (P less than or equal to 0.001). The adults had sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 8 publications
0
12
0
Order By: Relevance
“…Review and screening of initial articles plus manual crosschecks identified 63 source articles that met inclusion criteria and had extractable data. The source articles included 11 RCTs of AOM antibiotic versus placebo or no drug, 30–40 1 RCT of AOM homeopathy versus placebo, 41 9 cohort studies of restrictive antibiotics for AOM, 42–50 14 RCTs of recurrent AOM antimicrobial prophylaxis versus placebo or no drug, 51–64 1 cohort study of recurrent AOM natural history, 65 18 cohort studies of OME natural history, 66–83 2 RCT enrollment cohorts of OME therapy, 84,85 and 7 cohorts or RCT control groups of chronic OME natural history 86–92 …”
Section: Resultsmentioning
confidence: 99%
“…Review and screening of initial articles plus manual crosschecks identified 63 source articles that met inclusion criteria and had extractable data. The source articles included 11 RCTs of AOM antibiotic versus placebo or no drug, 30–40 1 RCT of AOM homeopathy versus placebo, 41 9 cohort studies of restrictive antibiotics for AOM, 42–50 14 RCTs of recurrent AOM antimicrobial prophylaxis versus placebo or no drug, 51–64 1 cohort study of recurrent AOM natural history, 65 18 cohort studies of OME natural history, 66–83 2 RCT enrollment cohorts of OME therapy, 84,85 and 7 cohorts or RCT control groups of chronic OME natural history 86–92 …”
Section: Resultsmentioning
confidence: 99%
“…The etiologies in adult OME include sinus infection, smoking, adenoid hypertrophy, barotraumas, NPC or radiation [11][12][13]. OME is common in both pre-irradiated and postirradiated NPC patients.…”
Section: Discussionmentioning
confidence: 99%
“…In adults, OME often develops following an upper respiratory tract infection, but in these cases early spontaneous resolution of the effusion(s) is common. 23 Cohen's model for the pathogenesis of OME fits most of the known facts concerning chronic OME. However, in cases where middle-ear effusions develop following air travel, it is difficult not to accept the notion that a failure of the eustachian tube to equalise the pressure inside and outside the middle ear during descent is the cause of the problem.…”
Section: Eustachian Tube Dysfunctionmentioning
confidence: 97%
“…Both forms of the disease have a similar spontaneous resolution rate during the first two months after presentation. 23 However, in some individuals, adult OME is a more chronic condition than its childhood counterpart. On the other hand, serous effusions are more common in adults and mucoid effusions are more common in children.…”
Section: Discussionmentioning
confidence: 99%